History and Role of Quality Accreditation - Russell, Tara A.; Ko, Clifford (Clinics in Colon and Rectal Surgery, 2023)
Accreditation has played a major role in the evolution of health care quality as well as the structure and organization of American medicine. In its earliest iterations, accreditation aimed to set a minimum standard of care, and now more prominently sets standards for high quality, optimal patient care. There are several institutions that provide accreditations that are relevant to colorectal surgery including the American College of Surgeons (ACS) Commission on Cancer, National Cancer Institute Cancer Center Designation, National Accreditation Program for Rectal Cancer, and the ACS Geriatrics Verification Program. While each program has unique criteria, the aim of accreditation is to assure high-quality evidenced-based care. In addition to these benchmarks, these programs provide avenues for collaboration and research between centers and programs.
Keywords: quality; accreditation; standards